Importance of guiding catheter disengagement during measurement of fractional flow reserve in patients with an isolated proximal left anterior descending artery stenosis. Issue 4 (25th June 2014) - Aminian, Adel; Dolatabadi, Dariouch; Lefebvre, Pascal; Khalil, Georges; Zimmerman, Robert; Michalakis, Georges; Lalmand, Jacques
<x xml:space="preserve">Abstract</x> Objective To determine the impact of ostial guiding catheter disengagement during measurement of fractional flow reserve (FFR) in patients with an isolated proximal left anterior descending artery (LAD) stenosis. Methods Measurements of FFR were performed in 21 patients with an isolated intermediate lesion of the proximal LAD. Proximal aortic pressure (Pa), distal post stenotic pressure (Pd), and Pd/Pa were recorded at baseline, after at least 90 sec of intravenous (IV) adenosine infusion with the guiding catheter still engaged in the coronary ostium (Pa1, Pd1, FFReng), and after at least 30 sec of guiding catheter disengagement back to the aorta (Pa2, Pd2, FFRdis). Results The average value of Pd/Pa at baseline was 0.92 ± 0.04. After 110 ± 8 sec of IV adenosine infusion, FFReng was 0.81 ± 0.07, which decreased to 0.77 ± 0.08 (FFRdis) after 38 ± 6 sec of guiding catheter disengagement. The mean ΔFFR (FFReng − FFRdis) was 0.05 ± 0.04. As compared to baseline values, the mean change in FFR values was significantly increased after disengagement of the guiding catheter (Pd/Pabaseline − FFRdis vs. Pd/Pabaseline − FFReng, 0.15 ± 0.05 vs. 0.10 ± 0.04, P < 0.0001). Before guiding catheter disengagement, eight patients (38%) had an FFR value ≤ 0.8. Following disengagement of the guiding catheter, the new FFR values decreased below 0.8 in six additional patients (28%), with subsequent change in treatment strategy. Conclusions During FFR assessment of isolated intermediate proximal LAD lesions, guiding catheter disengagement is associated with a decrease in mean FFR values. In patients with FFR values lying close to the treatment threshold, this can have an impact on treatment strategy. © 2014 Wiley Periodicals, Inc.